2019
DOI: 10.1590/0034-7167-2018-0165
|View full text |Cite
|
Sign up to set email alerts
|

Perception of women with breast cancer undergoing chemotherapy: a comprehensive analysis

Abstract: Objective: To comprehensively analyze the perception of women with breast cancer on the experience of undergoing chemotherapy. Method: This was a qualitative, descriptive, phenomenological study, supported by the Merleau-Ponty philosophy. It was conducted in a chemotherapy outpatient clinic with 20 participants who completed a phenomenological interview. Results: The phenomenological data analysis demonstrated that the perception of women about the experience of chemotherapy is about change, not only of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 13 publications
0
7
0
7
Order By: Relevance
“…In contrast to the higher level of suffering because of hair loss recorded in Latin and Asian women (Chou & Lu, 2019; Medeiros et al, 2019), Turkish women with breast cancer reported that losing a breast was the most destructive experience (Cebeci et al, 2012). In Turkish society, breasts are valued as the most important characteristic of women and, consequently, the surgical procedure to take them off makes them feel useless and less sexually attractive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to the higher level of suffering because of hair loss recorded in Latin and Asian women (Chou & Lu, 2019; Medeiros et al, 2019), Turkish women with breast cancer reported that losing a breast was the most destructive experience (Cebeci et al, 2012). In Turkish society, breasts are valued as the most important characteristic of women and, consequently, the surgical procedure to take them off makes them feel useless and less sexually attractive.…”
Section: Discussionmentioning
confidence: 99%
“…“It's weird , if you look in the mirror and see yourself without your hair , you lose some of your identity.” (Medeiros et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…É importante considerar que as modificações provocadas pelo tratamento oncológico no corpo das pacientes têm sido associadas a diversas experiências e impactos biopsicossociais do câncer. Em mulheres, frequentemente, essas modificações se relacionam com outros desfechos negativos em saúde 13 .…”
Section: Discussionunclassified